IMPLIKASI PEMBATALAN PERATURAN PRESIDEN NOMOR 53 TAHUN 2020 TERHADAP PENGELOLAAN KEUNGAN NEGARA - FAATHUR MUBARAQ; YAHYA AHMAD ZEIN; ARIF ROHMAN (JURNAL AKTA YUDISIA, 2025)
This study analyzes the Supreme Court’s decision in Case No. 12 P/HUM/2024, which annulled Presidential Regulation No. 53 of 2023 for contradicting the 1945 Constitution and financial management laws. The regulation, as a legal product, created unequal accountability between regional heads and legislatures, raising risks of injustice and misuse of funds. The Court emphasized that its drafting process lacked transparency and public participation, thus violating the principles of good governance. Although the annulment created temporary legal uncertainty in regional financial management, the government addressed the issue through a Joint Circular as transitional guidance. This decision highlights the importance of aligning legal products with constitutional values and reinforcing government governance based on rule of law, accountability, equality, and participation.